Material didáctico y su impacto psicomotriz en niños de 4 a 5 años en la Escuela Simón Bolívar Aspiazu Brunis del Cantón Babahoyo de la Provincia de Los Ríos periodo lectivo 2019-2020 - Espinoza Almeida, Genesis Carolina (2020)
Line of research, Education and social development, human talent, education and teaching, teaching, creativity in the teaching-learning process, the researcher aims to make a detailed analysis of all the shortcomings and mismatches caused by the lack of didactic material and its Psychomotor impact on children from 4 to 5 years old at the Simón Bolívar Aspiazu Brunis school. The specific objectives are to diagnose the situation in which children find themselves regarding the handling of the Didactic Material, the variables will be identified, within the theoretical framework a bibliographic foundation was made; The methodology that was used is based on the direct collection of information through the survey; using types such as exploratory, descriptive and correlated; The variables are operationalized: The independent. Teaching Materials and the dependent Development of Psychomotor. It is proposed to design a didactic guide to develop the Psychomotor skills of children and improve their skills and abilities.